2012
DOI: 10.1038/onc.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase CHIP regulates c-Myc stability and transcriptional activity

Abstract: c-Myc is a proto-oncogenic transcription factor and its rapid turnover mediated by the ubiquitin-proteasome system is critical for maintaining normal cellular homeostasis. Multiple ubiquitin ligases have been assigned for c-Myc regulation till date. However, the available data suggest for the possible existence of additional E3 ligase(s). Here, we report a new E3 ligase for c-Myc, the carboxyl terminus of Hsc70-interacting protein or CHIP, which is a chaperone-associated Ubox-containing E3 ligase. In this repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 43 publications
2
111
1
1
Order By: Relevance
“…Some ubiquitin ligases (CHIP) link chaperones and the 26S proteasome machinery by ubiquitinating chaperone substrates and channeling them toward the proteasome (76)(77)(78). Chaperones are among the proteins increased to the highest levels (ϳ16.7-to 27-fold) in the MAM of HCMV-infected cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Some ubiquitin ligases (CHIP) link chaperones and the 26S proteasome machinery by ubiquitinating chaperone substrates and channeling them toward the proteasome (76)(77)(78). Chaperones are among the proteins increased to the highest levels (ϳ16.7-to 27-fold) in the MAM of HCMV-infected cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent ubiquitin ligase to be identified for MYC is CHIP (carboxyl terminus of Hsc70-interacting protein) (Paul et al 2013). CHIP is a chaperone-associated U-box-containing E3 ligase that links a chaperone to the 26S proteasome machinery by ubiquitinating chaperone substrates and directing them toward the proteasome (Ballinger et al 1999).…”
Section: Chipmentioning
confidence: 99%
“…20 Several E3 ligases, including FBW7, SKP2, TRUSS, HectH9, β-Trcp1 and Hsc70-interacting protein (CHIP), have been identified as responsible for c-Myc degradation. 19,[22][23][24][25][26][27][28] However, it is still unclear whether c-Myc stability is regulated by ubiquitin-independent pathways. In the present study, we demonstrated that proteasome activator REGγ is a novel negative regulator of c-Myc and provided evidence that this regulation is evolutionarily conserved.…”
mentioning
confidence: 99%